The art of commemoration in the Renaissance : the Slade Lectures - Lavin, Irving, 1927-2019 (Italica press studies in art and history series, 2020)
"In the early 1980s, Irving Lavin delivered The Slade Lectures at Oxford University exploring his idea that the Italian fifteenth-century revival of ancient art was an outward sign of fundamental changes in humanity's perception of the inner self. This volume publishes for the first time six essays, which he based on those lectures and which he continued to work on until his death in 2019: Memory and the Sense of Self; On the Sources and Meaning of the Renaissance Portrait Bust; On Illusion and Allusion in Italian Sixteenth-Century Portrait Busts; Great Men Past and Present; Equestrian Monuments; and Collective Commemoration and the Family Chapel"--